A simple system to determine who needs osteoporosis screening - Sedaghat M; Soltani A; Hamidi Z; Rahimi E; Larijani B (Payesh, 2004)
Objective(s): To develop and validate a clinical tool to help physicians to identify which women are at increased risk for osteoporosis and should therefore undergo further testing with bone densitometry. Methods: Using the Endocrine and Metabolism Research Center (EMRC) database and postmenopausal women in Iranian Multicenter Osteoporosis Study (IMOS) who had undergone testing with dual-energy x-ray absorptiometry (DEXA) at femur and lumbar spine (L1-L4). The main outcome measure was low bone mineral density (T score of 2.5 or more standard deviations below the mean for yoi. ng adult women) at femur, Lumbar spine or both sites. Logistic regression analysis was used to identify the simplest algoritlun that would identify women at increased risk of low bone mineral density. Results: The study population comprised 4229 individual of whom 2148 women with menopause were selected; and 185 postmenopausal women from (IMOS) were also included. A simple algorithm based on age, weight, duration of menopause was developed. Validation of this 3 - item Iranian Osteoporosis Scoring System (IOSS) showed that the tool had a sensitivity of 61.7% and specificity of 72.4% for women with osteoporosis. Conclusion IOSS can identify the majority of women likely to have low bone mineral density and is effective in substantially decreasing the need for all women to undergo DEXA testing.